Succeeding with autism : hear my voice - Cohen, Judith H. (Jessica Kingsley Publishers, 2005)
'One day I naively asked Michael what's it like to be autistic. He replied, ''I don't know. I've always been autistic.'''.-from Succeeding with Autism. Michael is a young man who has succeeded in managing his autism and is experiencing success in life despite a diagnosis that might have predicted only disability and despair. He did not talk in early childhood and displayed the classic traits of a severely autistic child, but he has broken out of his silence to help others to learn from his insights and experiences. An explosion of newly diagnosed cases of autism has resulted in a keen interes.